Development of a Resilience Measurement Tool: Adaptation of the Resilience Scale for Adolescents - Stefani Virlia; Cita Tri Kusuma (Universitas PGRI Yogyakarta, 2026)
The increasing psychological challenges faced by Indonesian adolescents highlight the need for a culturally appropriate and psychometrically robust measure of resilience. This study aimed to adapt and validate the Rugged Resilience Measure (RRM) for adolescents within the Indonesian cultural and linguistic context. The adaptation procedure followed standardized guidelines, including forward translation, back translation, synthesis, and expert equivalence review. Data were collected from 1.091 adolescents aged 12–15 years, and Confirmatory Factor Analysis (CFA) was conducted to examine the construct validity of the adapted scale. Results showed that all items demonstrated satisfactory factor loadings (0.700–0.808), and the unidimensional instrument demonstrated good fit (CFI = 0.952; TLI = 0.938; RMSEA = 0.088; SRMR = 0.032). The instrument also showed strong internal consistency (α = 0.920). These findings support the validity and reliability of the Indonesian version of the RRM and provide an evidence-based tool for understanding adolescent resilience amid rapid digitalization and developmental challenges. The adapted measure offers practical value to researchers, educational institutions, and policymakers in designing programs and interventions to strengthen adolescent mental health. Keywords: instrument adaptation, resilience, adolescents, RRM